Discharge Planning and Home Care Needs Assessment for Older Patients in a Nursing Hospital - Lina Urbietė; Vita Lesauskaitė; Jūratė Macijauskienė (Medicina, 2020)
Background and objectives: Following the accumulation of a sufficient amount of scientific evidence, it is now possible to appeal for changes in the organization of nursing services. Our aims are to assess the health status of patients discharged from nursing hospitals and to identify their home care needs by applying the international InterRAI Home Care (HC) assessment form. Material and methods: 152 geriatric patients (older than 65 years of age) discharged after a 90−120-day stay at a nursing hospital were examined using face-to-face interviews. The data from the medical records were also assessed. The capacities of patients were discussed with the patients themselves, nursing personnel, and relatives of the patients. Results: The analysis revealed that 45.4% of the respondents had severely impaired cognitive skills, while 27.6% had moderately impaired cognitive skills for decision making in daily living. People with greater cognitive difficulties were more dependent during daily instrumental activities and ordinary daily activities. The strongest relationship was established among the cognitive skills and management of medications, management of finances, and ordinary housework. For the greater part of respondents, a special need for permanent nursing (57.9%) or assistance (25.7%) was determined, i.e., official, state-funded nursing at home was appointed. The remaining respondents (16.4%) were not appointed further state-funded nursing or assistance at home, but an assessment of the independence of these patients based on the InterRai Activities of Daily Living Hierarchy Scale indicated that these skills varied from moderate independence (decision making was difficult only in new situations) to severely impaired skills (made no independent decisions or they were scarce). Despite the low independence of respondents, the majority of them would prefer nursing services at home to institutional nursing. Conclusions: The low independence observed in all participants, as well as their limited capacities, prove the need for nursing services at home and the necessity of their continuity. Despite the low independence of respondents, the majority of them would prefer nursing services at home to institutional nursing.